2015
DOI: 10.1038/nn.4199
|View full text |Cite
|
Sign up to set email alerts
|

The indirect pathway of the nucleus accumbens shell amplifies neuropathic pain

Abstract: We examined adaptations in nucleus accumbens (NAc) neurons in mouse and rat peripheral nerve injury models of neuropathic pain. Injury selectively increased excitability of NAc shell indirect pathway spiny projection neurons (iSPNs) and altered their synaptic connectivity. Moreover, injury-induced tactile allodynia was reversed by inhibiting and exacerbated by exciting iSPNs, indicating that they not only participated in the central representation of pain, but gated activity in ascending nociceptive pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
190
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(214 citation statements)
references
References 24 publications
20
190
4
Order By: Relevance
“…2A): a result consistent with evidence showing that dopamine receptor expression decreases in the NAc following an SNI injury and with a drop of dopamine concentration in the NAc after SNI injury (Ren et al 2016). More important, we observed that NAc shell indirect spiny neurons show increased excitability and decreased dendritic fields within days after SNI injury and that oral treatment with L-DOPA and naproxen blocks the effects of SNI on excitability, dendritic architecture, and synaptic connectivity and blunts neuropathic pain (Ren et al 2016).…”
Section: Therapeutic Interventions For Preventing Chronic Painsupporting
confidence: 90%
See 2 more Smart Citations
“…2A): a result consistent with evidence showing that dopamine receptor expression decreases in the NAc following an SNI injury and with a drop of dopamine concentration in the NAc after SNI injury (Ren et al 2016). More important, we observed that NAc shell indirect spiny neurons show increased excitability and decreased dendritic fields within days after SNI injury and that oral treatment with L-DOPA and naproxen blocks the effects of SNI on excitability, dendritic architecture, and synaptic connectivity and blunts neuropathic pain (Ren et al 2016).…”
Section: Therapeutic Interventions For Preventing Chronic Painsupporting
confidence: 90%
“…A cellular/molecular study of NAc shell neurons revealed the mechanistic role of dopamine in the transition to chronic pain (Ren et al 2016), suggesting therapeutic potential.…”
Section: Therapeutic Interventions For Preventing Chronic Painmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, tactile allodynia was reversed by inhibiting and exacerbated by exciting these neurons. This suggests that neurons in the nucleus accumbens not only participate in the central representation of pain, but that they may gate activity in ascending pathways associated with expression of neuropathic pain in higher centers (Ren et al, 2016).…”
Section: H Role Of Mesolimbic Reward Circuitrymentioning
confidence: 99%
“…His team has also shown that the main determinant of chronic pain is not the injury, but the properties of the person's brain, he adds. And, in rodents, the researchers have been able to block the transition from acute to chronic pain using drugs that inhibit neurons in the nucleus accumbens 7 ; a trial is under way to see if this works in humans. "I'm confident we will quickly develop a whole series of new treatment options specific for different types of chronic pain, " says Apkarian.…”
Section: Mind Over Miserymentioning
confidence: 99%